Peningkatan kompetensi pedagogi dan pengembangan konten digital guru berbasis "GaleriMu" - Rahmawati, Laili Etika; KHOLID, MUHAMMAD NOOR; Prasetyo, Wibowo Heru; Al Irsyadi, Fatah Yasin; Lestari, Winda Dwi; Beauty, Melati (Jurnal SOLMA, 2025)
In the 21st century, elementary school teachers need to have skills in designing active learning by implementing technology. Teachers who are able to integrate technology with active learning strategies not only improve their understanding of concepts, but also prepare their students to face future challenges. The activity was carried out to train teachers of Muhammadiyah Elementary Schools in Surakarta in designing active learning and using digital media. The activity was attended by 175 teachers of Muhammadiyah Elementary School in Surakarta. The form of activity is in the form of a workshop with a duration of 40 hours face-to-face and independently. The service team and teachers together learn to implement active learning and create digital learning media. The venue for the implementation at the University of Muhammadiyah Surakarta will be from December 2024 to January 2025. The results of the activity were to increase the understanding of Muhammadiyah Elementary School teachers in Surakarta in implementing an active learning model, creating digital learning content, and building a space to store digital learning content called "GaleriMu". The activity succeeded in improving teachers' skills in designing active learning using digital content and the existence of a storage space for digital learning content.